Advancing the Analysis of Past Human/Plant Relationships: Methodological Improvements of Artefact Pollen Washes. (12th March 2018) - Miras, Y.; Ejarque, A.; Barbier‐Pain, D.; Corbineau, R.; Ledger, P. M.; Riera Mora, S.; Garreau, A.; Voldoire, O.; Allain, E.; Mangado Llach, J.; Sánchez De La Torre, M.; Martínez‐Grau, H.; et al.
Abstract : The 'pollen washes' technique, based on the analysis of the pollen embedded in the porous surface of archaeological artefacts, is developed for investigating past plant usage and consumption and to characterize the functionality of artefacts related to plant processing, gathering and storage. The research presented results in relevant methodological improvements of this technique, which has never previously been applied on materials from European contexts. The improvements allow: (1) faster analysis of a broad series of artefacts or those with large use‐surface areas likely to retain more pollen; and (2) a more thorough, deeper and precise cleaning method, allowing the study of smoother artefacts. Finally, the recovery of Trifolium ‐group pollen from a macro‐lithic tool from Xicotó rock shelter (Montsec ranges, Spain) demonstrates that the pollen washes technique can reveal new insights into both the use and consumption of wild and domestic plants by prehistoric societies, and the functionality of archaeological objects whose interpretation is still problematic.